A methodology for mining material properties with unsupervised learning. (30th November 2009) - Al-Mubaid, Hisham; Abouel Nasr, Emad S.; Hussein, Mohammed
Studying material properties from a data mining perspective can be beneficial for manufacturing and other industrial engineering applications. We present new ways to utilise data mining and machine learning in analysing material properties with experimental study. This work employs an effective feature reduction technique with clustering and classification to extract the most significant properties of the materials which can benefit various manufacturing industries. We conducted the experiments on five material datasets. The evaluation results proved that: 1) The feature reduction technique is quite effective in reducing the features to 20 or ten by removing all non-significant and redundant features. Thus, this model represents an effective way of extracting the most significant features for each class of materials. 2) The material databases and properties can be easily and feasibly analysed and examined in data mining and the outcomes can be very useful for the manufacturing industries and other industrial engineering applications.